2021
DOI: 10.1556/2006.2021.00082
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence of enhanced early attentional bias toward sexual images in individuals with tendencies toward cybersex addiction

Abstract: Background and aims Attentional bias is a key factor in addictive behavior maintenance. However, whether attentional bias has a similar effect on cybersex addiction is unclear. We investigated differences in the attentional processing of sexually explicit images between individuals with high tendencies toward cybersex addiction (TCA) versus low tendencies using behavioral and electrophysiological indices. Methods Twenty-eight individuals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…Currently, PIPU is not officially recognized as a mental disorder, and there are no universally accepted diagnostic criteria. Thus, participants were selected based on the top and bottom quartiles of PIPUS scores (e.g., Wang et al, 2021 ). According to this classification, 60 participants (30 in high tendencies toward PIPU group and 30 in low tendencies toward PIPU group) volunteered to attend the experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, PIPU is not officially recognized as a mental disorder, and there are no universally accepted diagnostic criteria. Thus, participants were selected based on the top and bottom quartiles of PIPUS scores (e.g., Wang et al, 2021 ). According to this classification, 60 participants (30 in high tendencies toward PIPU group and 30 in low tendencies toward PIPU group) volunteered to attend the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence suggests that PIPU is analogous to drug addiction or other behavioral addictions ( Seok and Sohn, 2015 ; Kowalewska et al, 2018 ; Stark et al, 2018 ). For example, PIPU is related to cue-reactivity for sex-related stimuli ( Brand et al, 2011 ; Voon et al, 2014 ; Wang et al, 2021 ), and this mechanism is also present in the development and maintenance of substance-related addictions (e.g., Skinner and Aubin, 2010 ). Moreover, neural activation toward sex- and drug-related stimuli involves similar brain networks, presumably modulated by the mesolimbic dopamine circuits ( Brand et al, 2016 ; Gola and Draps, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the construct of initial response to reward, we included fMRI [37•, 38, 39] and behavioral [40][41][42] studies using passive viewing paradigms, i.e., studies in which participants were asked only to view the sexual stimuli, sometimes with subsequent ratings, but without other behavioral tasks during the experiment. We further included behavioral studies using an approach-avoidance task (AAT; [43][44][45][46]), a dot probe task [47,48], and a stroop task [49,50].…”
Section: Initial Response To Rewardmentioning
confidence: 99%
“…The attentional bias for sexual words measured via reaction time in a stroop task [49] was also found to be positively related to a dimensional indicator of PPU. Finally, in a more recent stroop task using sexual images with colored frames, Wang et al found that a group with high scores on a PPU measure displayed a greater attentional bias towards sexual images via reaction time interference effects and event-related potentials compared to a group with low PPU scores [50].…”
Section: Initial Response To Rewardmentioning
confidence: 99%
“…There is growing evidence that PIPU resembles substance use disorder ( 9 , 10 ). For instance, previous studies have identified cue reactivity and craving as an important mechanism of PIPU ( 11 13 ) equally important for the development and maintenance of substance dependence ( 14 ). In addition, the neural processing of sexual- and substance-related cues relies on identical brain networks, possibly regulated by the mesolimbic dopamine system ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%